Selection of the best public fuel filling stations with analytical hierarchy process in Tangerang Regency - Sulistyono, Aries Andjar; Astuti, Pudji; Moengin, Parwadi (Operations Excellence: Journal of Applied Industrial Engineering, 2025)
Energy is one of the main factors in supporting mobility in activities. Gas Stations (SPBU) are one way that people can get energy. In its operations, gas stations must be able to provide the best service to consumers so that maintaining consumer loyalty. This study aims to be able to choose the best Gas Stations (SPBU) with Analytical Hierarchy Process (AHP) method. The criteria used are based on previous research and based on the results of expert analysis so that the selected criteria are used as a model in decision making, namely management, sales, services, facilities and variations of fuel products. For alternatives to be evaluated are 5 gas stations located in the Legok area, Tangerang, Banten. Based on the calculation of the pairwise criterion comparison matrix in the AHP method, eigenvalues are obtained to perform consistency tests. after processing and analysis, it is known that the highest criterion is service and the lowest is sales. And alternative calculation results obtained that the gas station 5 is the best alternative chosen.